Tradução e adaptação transcultural do Apraxia of Speech Rating Scale 3.5 - Santos, Dhébora Heloísa Nascimento dos (2021)
Introduction: In Brazil, there is an instrument for the diagnosis of speech and language disorders. The Apraxia of Speech Rating Scale (ASRS) is a scale that differentiates between speech apraxia, dysarthria and aphasia. This scale has excellent inter-judge reliability in its total score. Thus, it is necessary to start the validation process for Brazil. Aim:To translate and cross-culturally adapt the Apraxia of Speech Rating Scale version 3.5 to Brazilian Portuguese. Method: Validation study restricted to translation and cross-cultural adaptation. The following steps were carried out: translation and synthesis of translations; selection of the applicability of the scale synthesis by judges who were recruited for this purpose; of analysis and evaluation, which were identified and by the total individual Validity Index. Finally, a synthesis was equipped regarding semantic, idiomatic, experiential, conceptual, syntactic, grammatical and operational equivalences. Results: The sample used for validity analysis and content calculation consisted of 18 speech therapists. Equivalences were necessary after expert analysis. Orientation coefficients between 0.83 and 0.94 Six items obtained values greater than 0.9. The other items presented values between 0.8 and 0.9. The Content Validity Index per item and the compliance parameters were evaluated for all aspects. Conclusion: The Brazilian version of the Apraxia of Speech Rating Scale 3.5 presents semantic, idiomatic, experiential, conceptual and syntactic/grammatical equivalence in relation to the original, thus being suitable for the next validation steps.